Telemedicine diffusion in a developing Country The case of India (march 2004). - Pal, A. (IEEE Transactions on information technology in biomedicine)
Telemedicine (health-care delivery where physicians examine distant patients using telecommunications technologies) has been heralded as one of several possible solutions to some of the medical dilemmas that face many developing countries. In this study, we examine the current state of telemedicine in a developing country, India. Telemedicine has brought a plethora of benefits to the populace of India, especially those living in rural and remote areas (constituting about 70% of India's population). We discuss three Indian telemedicine implementation cases, consolidate lessons learned from the cases, and culminate with potential researchable critical success factors that account for the growth and modest successes of telemedicine in India.